Representation of 21st Century Literacy (4C) in the Folklore Ular N'Daung by Dian Kristiani - Nofia Angela; Yulian Dinihari; Arifin; Dewi Sari Sumitro (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the representation of 21st-century literacy, which encompasses four main competencies: critical thinking, creativity, collaboration, and communication (4Cs) in the folktale